2016
DOI: 10.1111/coa.12712
|View full text |Cite
|
Sign up to set email alerts
|

The surgical challenge of carotid artery and Fallopian canal dehiscence in chronic ear disease: a pitfall for endoscopic approach

Abstract: Objective Endoscopic procedures are becoming common in middle ear surgery. Inflammation due to chronic ear disease can cause bony erosion of the carotid artery and Fallopian canals, making them more vulnerable during surgery. The objective of this study was to determine whether or not chronic ear disease increases dehiscence of the carotid artery and Fallopian canals. Design Comparative human temporal bone study. Setting Otopathology laboratory. Participants We selected 78 temporal bones from 55 deceased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Pauna and colleagues found on serial histological sections an increased incidence of carotid canal dehiscence in temporal bones of deceased donors with chronic otitis media compared to a control group. 22 The dehiscence, which was frequently closer to the promontory, was larger in size and the bony wall (when present) was thinner compared to findings in non-diseased ears. On the other hand, in cases with active chronic otitis media the mucosa is usually scarred, hyperplastic and vulnerable with good blood supply so that its removal is performed under a suboptimal operative view.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pauna and colleagues found on serial histological sections an increased incidence of carotid canal dehiscence in temporal bones of deceased donors with chronic otitis media compared to a control group. 22 The dehiscence, which was frequently closer to the promontory, was larger in size and the bony wall (when present) was thinner compared to findings in non-diseased ears. On the other hand, in cases with active chronic otitis media the mucosa is usually scarred, hyperplastic and vulnerable with good blood supply so that its removal is performed under a suboptimal operative view.…”
Section: Discussionmentioning
confidence: 88%
“…Pauna and colleagues found on serial histological sections an increased incidence of carotid canal dehiscence in temporal bones of deceased donors with chronic otitis media compared to a control group 22 . The dehiscence, which was frequently closer to the promontory, was larger in size and the bony wall (when present) was thinner compared to findings in non‐diseased ears.…”
Section: Discussionmentioning
confidence: 98%
“…The estimate of proper ventilation of the middle ear and mastoid is important to verify the aeration at the time of the CT-scan. Among patients with chronic middle ear disease, the rate of dehiscence of the intern carotid artery and of the Fallopian canal increases significantly [3]. In this scenario, the prevalence of dehiscence of the latter ranges from 25 to 57% [4].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier histologic temporal bone study showed that in normal temporal bones without cholesteatoma or chronic otitis media, most ICA dehiscences occur at the level of the middle ear (57.14%) and less often at the level of the ET (42.85%). 5 Other ICA dehiscences, such as an ICA-cochlear dehiscence 4 or a dehiscence of the ICA in the middle ear associated with pulsatile tinnitus, 2 have been reported and should be taken in account in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%